THE ANALYSIS OF PROBLEMS ENCOUNTERED BY BEGINNER WRITER IN WRITING A SHORT STORY: A Case Study in Creative Writing Class - N. Y. Pratiwi (Indonesian Journal Of Educational Research and Review, 2019)
Creative process is the journey that a writer takes in order to create a piece of creative writing. During this process a writer, especially a beginner writer, encountered numerous obstacles which influence the writing performance. This study was aimed to analyze the problems faced by the students of Creative Writing course in Ganesha University of Education and describe how the students deal with the problems. The problems analyzed consist of three major aspects of writing fiction, namely literature elements, technical problems, and students’ self-perception. The study found out that the majority of the students experienced similar problems from certain elements, meanwhile there were also problems found that appeared to be different from one another. This leads to further findings that the students conducted various attempts to deal with the problems..